Old and Novel Enteric Parvoviruses of Dogs - Paolo Capozza; Alessio Buonavoglia; Annamaria Pratelli; Vito Martella; Nicola Decaro (Pathogens, 2023)
Parvovirus infections have been well known for around 100 years in domestic carnivores. However, the use of molecular assays and metagenomic approaches for virus discovery and characterization has led to the detection of novel parvovirus species and/or variants in dogs. Although some evidence suggests that these emerging canine parvoviruses may act as primary causative agents or as synergistic pathogens in the diseases of domestic carnivores, several aspects regarding epidemiology and virus–host interaction remain to be elucidated.